Artificial Reefs: Solution for Restoration of Marine Ecosystem and Improving Community Resilience - Rani, Susmita; Kumar, Sarvendra; Kumar, Pankaj; Abhiman; Dar, Showkat Ahmad; Kumar, Abhishek (International Journal of Bio-resource and Stress Management, 2025)
Pollution and global warming have become a threat to the environment and sustenance of life existing on earth. It has led to climate change causing a shift in habitat and ecology of species residing over. Effect of climate change is immense on marine life and it has affected the aquatic flora and faunas, adversely. Therefore, there has been increasing interest in marine restoration. Artificial reefs implementation is one approach being used as a measure for marine ecosystem restoration that has been damaged due to coral reefs destruction by anthropogenic activities like pollution, overfishing, destructive fishing using cyanide or dynamite, collecting live corals for aquarium market, etc. Artificial reefs are modeled by sinking oil rigs, scuttling ships, or shipwrecks that help in preservation of the ocean floor by mimicking with natural reefs. They may be built of polyvinyl chloride or concrete to provide substratum for attachment of algae and invertebrates such as barnacles, corals, and oysters which in turn provides intricate structures and food for assemblages of fish. In addition, they provide livelihoods to millions of people and serve as barrier against the worst impact of cyclones, protecting the coastal communities. These reefs cater to the needs of recreational fishermen and tourists so that the natural reefs can be completely conserved and relieved of fishing pressure. Henceforth, this comprehensive literature review on artificial reefs is carried out to understand its role in marine ecosystem restoration and fisheries management, alongwith the study of its design, material characteristics, application, effectiveness and management.